ISLAMIC STATE UNIVERSITY RESPONSES TO THE COVID 19 IN LEARNING - Ahmad Bustomi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
Abstarct Defiance faced by Islamic State University in this era is Covid 19. The purpose of this discourse is to explain how response of Islamic State University to Covid 19 in learning which consist of learning method in Islamic State University. Research approach utilize qualitative descriptive method. Qualitative research more emphasis to interpreating rather than generalitation. Base on this approach, researcher will interpreate meaning from Islamic State University activities. Kind of this research is Field research. it is research form to explain the meaning given by society in activity and reality in Islamic State University as reaction of covid 19 in learning. Technique to determine the informan utilize Purposive Sampling technique.. Data collecting uses interview, observation and documentation. All data will be checked the validity by triangulation technique and then analized by data reduction process, data display anad the last conclution. In pandemic covid 19 era, response of Islamic State University is learning by online class/online learning. Online learning is process to transform conventional education into digital form which has their own problem and their own occassion. Online class can be devided two ways. Its are syncronus method and asynchronous method as response. Synchronous can utilize Skype, Zoom Meeting, Google Meet, Cloudx or WhasApp Video Call meanwhile asynchronous method utilizes Google Classroom and Learning management System (LMS). Keyword: Islamic State University, Responses, Covid 19, Learning